Characterization of Essential oil from Foeniculum vulgare Mill (Apiaceae) in the Souk Ahras Region (North-East of Algeria). - Bessioud Hana; Gheris Sabrina (My University, 2022)
Foeniculum vulgare Mill. Is a major aromatic plant belonging to the family (Umbelliferae / Apiaceae), commonlyknownasfennelisawell-knownandimportantmedicinalandaromaticplantwidelyusedascarminative, digestive,diureticandintreatingrespiratoryandgastrointestinaldisordersintheSoukAhrasregion.Thepresentstudywas conductedtodeterminethedifferencesinplantpropertiesintermsofessentialoilcontentandphytochemicalscomposition. Theessentialoilswereisolatedfromtheaerialparts(leafandstem)ofthefennelplant(FoeniculumvulgareMill.)byhydro distillation,wheretheyieldofessentialoilsfromthedryplantmatterwas0.96%.Thisstudyshowsthatthemajor componentsoftheessentialoilthatallowedidentificationbyGC-MSconsistmainlyofamixtureofα-Phellandrene26.405% and D-Limonene (19.852%) ;β-Myrcene (11.951%) ; ɣ- Terpinene (8.182%) ; Terpinolene (5.069%) ; β-Phellandrene (4.745%);trans-Piperitoneepoxide(2.644%);Myristicin(2,530%).Inaddition,thephytochemicalsscreeningoftheaerial parts allowed to highlight the presence of Secondary metabolites in the plant tissues such as : polyphenols, Flavonoids٫Tannins,coumarins,andterpenes.However,thetestscamebacknegativeforSaponosides,Sterols,carotenoidsandalkaloids. Thepresentstudyconcludedbyprovingthatthefennelplantisrichineffectivechemicalcomponentsthatcan beusedinseveralmedical,industrialandfoodfields,whichmakesitaprofitableeconomicsourceifitiswellexploitedin the Souk Ahras region. ---------------------------------------------------------------------------------------------------------------------------------------------------------------- MillvulgareFoeniculumهونباتعطريرئيسيينتميإلىعائلةالخيمياتApiaceae(/)Umbelliferae؛والمعروفباسمالشمرو هونباتطبيوعطريفعالجدايستخدمعلىنطاقواسعكطاردللريحمنالجهازالهضميومدرللبولوفيعالجاتاضطراباتالجهازالتنفسيوالجهازالهضميفيمنطقةسوقاهراس.أجريتالدراسةالحاليةلتحديداالختالفاتالموجودةفيخصائصالنباتمنحيثمحتوىالزيتالعطريوتركيبالمواد الكيميائيةالنباتية.اينتمعزلالزيوتاألساسيةمناألجزاءالهوائية(ورقةوساق)مننباتالشمرMill(vulgare).Foeniculumبالتقطيرالمائي،حيثبلغمحصولالزيوتاألساسيةمنالمادةالنباتيةالجافة0.96٪،كماتوضحهاتهالدراسةأنالمكوناتاألساسيةللزيتالعطريالتيسمحالتعرفعليهابواسطة ٪8.182تيربينيني-ɣ؛٪β-Myrcene11.951؛D-Limonene19.852٪؛α-Phellandrene26.405:منخليطمنأساسيبشكليتكونGC/MS ؛تيربينولين5.069٪؛-βفيالندرين4.745٪؛إيبوكسيدترانسبيبيريتون2.644٪؛ميريستيسين530،2٪.باإلضافةالىذلكسمحفحصالموادالكيميائية النباتيةلألجزاءالهوائيةبإبرازوجودالمستقلباتالثانويةفيأنسجةالنباتمثل:البوليفينول،الفالفونويد،التانينات،الكومارين،والتربينات.ومعذلك،جاءت نتائجاالختباراتسلبيةبالنسبةللسابونوزيداتوالستيرولوالكاروتيناتوالقلويدات خلصتالدراسةإليإثباتأننباتالشمرغنيبالمكوناتالكيمائيةالفعالةالتييمكناستخدامهافيعدةمجاالتطبيةصناعيةوغذائيةممايجعلها مصدراقتصاديمربحإذاتماستغاللهابشكلجيدفيمنطقةسوقاهراس. ------------------------------------------------------------------------------------------------------------------------------------------------------------------ Foeniculum vulgare Mill. Est une plante aromatique majeure appartenant à la famille (Umbelliferae/Apiaceae), communémentappeléefenouilestuneplantemédicinaleetaromatiquebienconnueetimportantelargementutiliséecomme carminatif,digestif,diurétiqueetdansletraitementdestroublesrespiratoiresetgastro-intestinauxdanslarégiondeSouk Ahras.Laprésenteétudeaétémenéepourdéterminerlesdifférencesdanslespropriétésdesplantesentermesdeteneuren huileessentielleetdecompositionphotochimiques.Leshuilesessentiellesontétéisoléesdespartiesaériennes(feuilleettige )delaplantedefenouil(FoeniculumvulgareMill.)parhydrodistillation,oùlerendementenhuilesessentiellesdelamatière végétale sèche était de 0,96 %. Cette étude montre que les composants majeurs de l'huile essentielle ayant permis l'identification par GC-MS sont constitués principalement d'un mélange d'α-Phellandrène 26,405% et de D-Limonène (19,852%);β-Myrcène(11,951%);ɣ-Terpinène(8,182%);Terpinolène(5,069%);β-Phellandrène(4,745%);époxydede trans-pipéritone(2,644%);Myristicine(2530%).Deplus,lecriblagephotochimiquesdespartiesaériennesapermisde mettreenévidencelaprésencedemétabolitessecondairesdanslestissusvégétauxtelsque:lespolyphénols,lesflavonoïdes, lestanins,lescoumarinesetlesterpènes.Cependant,lestestssontrevenusnégatifspourlessaponosides,lesstérols,les caroténoïdes et lesalcaloïdes. Laprésenteétudeaconcluàprofitenprouvantquelaplantedefenouilestricheencomposantschimiques efficacespouvantêtreutilisésdansplusieursdomainesmédicaux,industrielsetalimentaires,cequienfaitunesource économiquecapablesielleestbienexploitéedanslarégiondeSoukAhras.